AMPHIBIA, ANURA, HYLIDAE, Trachycephalus atlas Bokermann, 1966: NOVO REGISTRO E COMENTÁRIOS SOBRE A DISTRIBUIÇÃO GEOGRÁFICA - Jr., Arnaldo José Correia Magalhães; Barbosa, Abraão Ribeiro; Jr., Severino Mendes de Azevedo; Pinho, Milena Sardou; Beltrão, Mayara Guimarães; Alves, Brygida Carolyne Freire (Revista Nordestina de Zoologia, 2011)
12 specimens of Trachycephalus atlas Bokermann, 1966 specie have bee captured in three different locations in Alagoas, Sergipe and Paraíba states, constituting the first record published of this species for these States and expanding the geographic distribution 150 km of the origin distribution. Besides of this record, are discussed here some comments about the distribution of T. atlas suggesting that its distribution correlates to specify environents of the Caatinga Biome and to transition areas in which the species were first recorded.